Hepatitis C virus quasispecies and pseudotype analysis from acute infection to chronicity in HIV-1 co-infected individuals - Ferns, R. Bridget; Tarr, Alexander W.; Hue, Stephane; Urbanowicz, Richard A.; McClure, C. Patrick; Gilson, Richard; Ball, Jonathan K.; Nastouli, Eleni; Garson, Jeremy A.; Pillay, Deenan (Elsevier, 2016)
HIV-1 infected patients who acquire HCV infection have higher rates of chronicity and liver disease progression than patients with HCV mono-infection. Understanding early events in this pathogenic process is important. We applied single genome sequencing of the E1 to NS3 regions and viral pseudotype neutralization assays to explore the consequences of viral quasispecies evolution from pre-seroconversion to chronicity in four co-infected individuals (mean follow up 566 days). We observed that one to three founder viruses were transmitted. Relatively low viral sequence diversity, possibly related to an impaired immune response, due to HIV infection was observed in three patients. However, the fourth patient, after an early purifying selection displayed increasing E2 sequence evolution, possibly related to being on suppressive antiretroviral therapy. Viral pseudotypes generated from HCV variants showed relative resistance to neutralization by autologous plasma but not to plasma collected from later time points, confirming ongoing virus escape from antibody neutralization.